The global, regional, and national alcohol-related colorectal cancer burden and forecasted trends: results from the global burden of disease study 2021 - Yao, Jinfeng; Chen, Guo (Frontiers in Nutrition, 2024)
BackgroundThe mortality of colorectal cancer (CRC) is increasing year by year and poses a significant global health burden. Many studies have demonstrated that alcohol consumption is an important risk factor for CRC and is closely associated with malignant metastasis in CRC patients, which in turn leads to a poor prognosis.MethodsThis study aimed to quantify the global, regional, and national burden of alcohol-related CRC between 1990 and 2021. First, numbers and age-standardized rates of deaths and disability-adjusted life years (DALYs) for alcohol-related CRC in 2021 were analyzed at different levels. Temporal trends in the burden of disease from 1990 to 2021 were analyzed through linear regression models. Finally, both Age-Period-Cohort (APC) models and Bayesian Age-Period-Cohort (BAPC) models were utilized to project the future burden of the disease for 2022–2046.ResultsThe global burden of disease for alcohol-related CRC is higher in 2021 compared to 1990. Male and older age groups are at high risk. Disease burden varies very much between Sociodemographic Index (SDI) regions, Global Burden of Disease (GBD) regions and countries. From 1990 to 2021, the number of cases increased, but the Age-Standardized Rate (ASR) decreased. The trends in disease burden predicted by the two models for 2022–2046 were not consistent.ConclusionThis study describes the burden of disease in alcohol-related CRC and emphasizes that alcohol is a non-negligible risk factor for CRC. In order to mitigate harm, we need to strengthen disease surveillance, early prevention, timely detection, and improved treatment measures, with different approaches and responses for different regions.